Exploring the relationship between stress and excessive gaming: the role of game efficacy - Lee, Yeungjeom (Deviant behavior, 2025)
Video game overuse, especially among youths, has become a global social concern with diverse adverse consequences. Using data on a sample of Korean adolescents from the Game User Panel, this study aims to enhance our understanding of the connection between stress and excessive gaming by integrating the concept of gaming efficacy. A series of cross-lagged dynamic panel models indicate that academic stress is significantly related to increased game use. Furthermore, this relationship is moderated by game efficacy. The findings suggest that video games may serve as a coping strategy, allowing adolescents to fulfill basic psychological needs by feeling confident in their gaming abilities. Limitations and suggestions for future studies are discussed.